Infrared and raman spectroscopies of clay minerals - Gates, W. P.; Kloprogge, J.T; Madejova, Jana (Developments in clay science, 2017)
Infrared and Raman Spectroscopies of Clay Minerals, Volume 8 in the Developments in Clay Science series, is an up-to-date overview of spectroscopic techniques used in the study of clay minerals. The methods include infrared spectroscopy, covering near-IR (NIR), mid-IR (MIR), far-IR (FIR) and IR emission spectroscopy (IES), as well as FT-Raman spectroscopy and Raman microscopy. This book complements the succinct introductions to these methods described in the original Handbook of Clay Science (Volumes 1, 1st Edition and 5B, 2nd Edition), offering greater depth and featuring the most important literature since the development and application of these techniques in clay science. No other book covers such a wide variety of vibrational spectroscopic techniques in a single volume for clay and soil scientists.--Provided by publisher.